Application of Gestational Blood Glucose Control During Perinatal Period in Parturients with Diabetes Mellitus: Meta-Analysis of Controlled Clinical Studies - Wang, Tingting; Zhang, Wei (Frontiers in Surgery, 2022)
BACKGROUND Gestational diabetes mellitus (GDM) is a common metabolic disorder. Hyperglycemia may cause gestational hypertension, increase the probability of infection, abnormal embryonic development and increase the abortion rate. Oral hypoglycemic drugs may be the another effective means of blood glucose control in addition to insulin injection. We included controlled clinical studies for meta-analysis to understand the effect of oral hypoglycemic drugs in gestational diabetes. Methods The databases were searched with the keywords "Glycemic control" & "gestational diabetes": Embase (January 2000-August 2021), Pubmed (January 2000-August 2021), Web of Science (January 2000-August 2021), Ovid (January 2000-August 2021) and ClinicalTrials.org to obtain the RCT literatures related to the treatment of gestational diabetes with oral hypoglycemic drugs, after screening, the R language toolkit was used for analysis. Results A total of 10 articles with a total of 1938 patients were included, 7 studies used metformin as an hypoglycemic agent. Meta-analysis showed that oral metformin had no significant difference in fasting blood glucose levels after intervention compared with insulin injection [MD=-0.35, 95%CI(-0.70,1.40), Z=0.66, P=0.51], no significant difference in postprandial blood glucose levels after intervention [MD=-2.20, 95%CI(-5.94,1.55), Z=-1.15, P=0.25], and no statistical difference in glycosylated hemoglobin [MD=0.10, 95%CI(-0.17,-0.04), Z=-0.94, P=0.31]. Metformin was more conducive to reducing maternal weight during pregnancy than insulin [MD=-1.55, 95%CI(-2.77,-0.34), Z=-2.5, P=0.0123], metformin reduced abortion rate compared with insulin [RR=0.81, 95%CI(0.63,1.05), Z=-2.61, P=0.015], and reduced cesarean section rate [RR=0.66, 95%CI(0.49,0.90), Z=-3.95, P=0.0001]. Discussion The application of oral hypoglycemic drug metformin in blood glucose control of gestational diabetes can play a hypoglycemic effect equivalent to insulin, and can control the weight of pregnant women, reduce the rate of abortion and cesarean section and improve pregnancy outcomes.